Analisis Efektivitas Failover Server Debian Menggunakan Heartbeat Cluster - Theresya Simanjuntak; Jelita Astrid Gulo; Lotar Mateus Sinaga (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
Service continuity is a critical requirement in modern network infrastructure, since even a brief interruption on a primary server can directly disrupt end-user access. This study examines the effectiveness of a failover mechanism built with Heartbeat Cluster on a Debian-based server environment. A two-node architecture was configured, consisting of Node1 as the primary (master) server and Node2 as the backup server, both monitored through Heartbeat to manage the automatic migration of a Virtual IP Address (VIP) whenever the primary node becomes unreachable. Testing was carried out by deliberately shutting down Node1 and measuring the time required for the system to transfer services to Node2 across six independent trials. The results show that Heartbeat consistently detected the failure and redirected the VIP without manual intervention, keeping the web service accessible with only a brief interruption; the average failover time recorded was 14.41 seconds. The system also performed a successful failback once Node1 was restored. These findings confirm that Heartbeat Cluster is an effective and low-cost approach for improving service availability on Debian servers, particularly for small-scale or educational network environments with limited infrastructure budgets.